Integrative Analysis of Fruit Quality and Anthocyanin Accumulation of Plum cv. ‘Cuihongli’ (Prunus salicina Lindl.) and Its Bud Mutation - Ling Liao; Yaman Li; Xuejiao Lan; Yiyue Yang; Wen Wei; Jinglan Ai; Xiangning Feng; Hongyu Chen; Yuhang Tang; Lijuan Xi; Zhihui Wang (Plants, 2023)
Fruit color is one of the quality indicators to judge the freshness of a plum. The coloring process of plum skin is valuable for research due to the high nutritional quality of anthocyanins found in plums. ‘Cuihongli’ (CHL) and its precocious mutant variety ‘Cuihongli Red’ (CHR) were used to analyze the changes of fruit quality and anthocyanin biosynthesis during plum development. The results showed that, during the development of the two plums, the total soluble solid and soluble sugar contents were highest at the mature stage, as the titratable acid trended gradually downward as the fruits of the two cultivars matured, and the CHR fruit showed higher sugar content and lower acid content. In addition, the skin of CHR turned red in color earlier than CHL. Compared with CHL, the skin of CHR had higher anthocyanin concentrations, higher activities of phenylalanine ammonia-lyase (PAL), chalcone isomerase (CHI), dihydroflavonol-4-reductase (DFR), and UDPglucose: flavonoid-3-O-glucosyltransferase (UFGT), and higher transcript levels of genes associated with anthocyanin production. In the flesh of the two cultivars, no anthocyanin content was detected. Taken together, these results suggest that the mutation exerted a major effect on anthocyanin accumulation via modification of the level of transcription; thus, CHR advances the ripening period of ‘Cuihongli’ plum and improves the fruit quality.